2019
DOI: 10.1039/c8ob02394h
|View full text |Cite
|
Sign up to set email alerts
|

A convenient and reproducible method for the synthesis of astatinated 4-[211At]astato-l-phenylalanineviaelectrophilic desilylation

Abstract: Electrophilic desilylation allows for convenient and reproducible synthesis of the aromatic amino acid derivative 4-[211At]astato-l-phenylalanine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In addition, we used a borono-precursor to achieve the 211 At labeling of PA. This preparation method proceeded efficiently under mild conditions in aqueous media and did not require any toxic reagents, in contrast to previous work [12][13][14].…”
Section: Discussionmentioning
confidence: 88%
“…In addition, we used a borono-precursor to achieve the 211 At labeling of PA. This preparation method proceeded efficiently under mild conditions in aqueous media and did not require any toxic reagents, in contrast to previous work [12][13][14].…”
Section: Discussionmentioning
confidence: 88%
“…Although initially developed with organomercuric derivatives [ 102 ], trialkylaryltin were preferred, Sn(alkyl) 3 being good leaving groups associated to a lower toxicity [ 103 ]. Recently, silicon derivatives were proposed as possible alternative to stannylated compounds [ 104 ]. The other approach is based on the At − species, presented to be easier to handle due to a larger predominance domain than At + .…”
Section: Astatine-211mentioning
confidence: 99%
“…Phenylalanine has been previously labeled with 211 At using different methods 3 5 . However, most of these methods have certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…They also prepared [ 211 At]APA by the electrophilic destannylation of N -Boc-4-tributylstannyl-L-phenylalanine; however, the organic tin compound used in this reaction is hazardous for the environment. Watanabe et al recently reported the synthesis of [ 211 At]APA via electrophilic desilation; the corresponding 211 At-labeled triethylsilyl substituted precursor was heated at 70 ℃ for 10 min in a methanol–trifluoroacetate solvent mixture 5 . The overall radiochemical yield in this method was in the range 65–85%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation